Portable speaker (Chopa) / Nur Elliana Fauzi - Fauzi, Nur Elliana (Universiti Teknologi MARA, Kedah, 2018)
Chopa design concept to design a speaker with safety measures that can be used by all ages. To design a modern and minimal design. Design Statement To design a modern and minimal design portable for all ages. Problem Identification - Not really comfortable to hold. - Have a lot of edges.